Emerging Potential of Exosomal Non-coding RNA in Parkinson’s Disease: A Review - Zhang, Peng; Rasheed, Madiha; Liang, Junhan; Wang, Chaolei; Feng, Lin; Chen, Zixuan (Frontiers in Aging Neuroscience, 2022)
Exosomes are extracellular vesicles that are released by cells and circulate freely in body fluids. Under physiological and pathological conditions, they serve as cargo for various biological substances such as nucleotides (DNA, RNA, ncRNA), lipids, and proteins. Recently, exosomes have been revealed to have an important role in the pathophysiology of several neurodegenerative illnesses, including Parkinson’s disease (PD). When secreted from damaged neurons, these exosomes are enriched in non-coding RNAs (e.g., miRNAs, lncRNAs, and circRNAs) and display wide distribution characteristics in the brain and periphery, bridging the gap between normal neuronal function and disease pathology. However, the current status of ncRNAs carried in exosomes regulating neuroprotection and PD pathogenesis lacks a systematic summary. Therefore, this review discussed the significance of ncRNAs exosomes in maintaining the normal neuron function and their pathogenic role in PD progression. Additionally, we have emphasized the importance of ncRNAs exosomes as potential non-invasive diagnostic and screening agents for the early detection of PD. Moreover, bioengineered exosomes are proposed to be used as drug carriers for targeted delivery of RNA interference molecules across the blood-brain barrier without immune system interference. Overall, this review highlighted the diverse characteristics of ncRNA exosomes, which may aid researchers in characterizing future exosome-based biomarkers for early PD diagnosis and tailored PD medicines.